Import Independence is the Main Factor of Economic Independence of the Russian Economy - V. Moiseev, Vladimir; V. Yagudina , Elena; P. Tubaltsev, Timur; Kostychev, Mikhail Yu. (Journal of Ecohumanism, 2024)
The economic security of the state is a complex and multifaceted structure. Being a part of the national security system, it simultaneously forms the basis for the formation of all elements included in its structure: military, technological, food, environmental and other security. Independence from imports ensures economic sovereignty and directly affects the degree of independence of the national economy, while ensuring economic security in difficult geopolitical conditions. Import independence is a state of the national economy that Russia must achieve in order to ensure its economic, food, military and other security while refusing imports, thereby strengthening its economic and national sovereignty. However, the lack of financial and material resources, political instability, and economic crises they haven’t allowed it yet for the full implementation of programs and plans in this area.